RELATIONAL LOGIC DATABASE DESIGN MODEL OF INFORMATION SYSTEM CONTROL PROJECT IN PT.ISTAKA KARYA - Luhur Kuswahyu; Djoko Harmantyo, DR., M.Sc Djoko Harmantyo, DR., M.Sc (Jurnal Sistem Informasi, 1990)
Analyzing this data is to provide a clearer picture about the functions of the dataelement or attribute is being investigated. After it was done depiction of therelationship (relationship) of an existing entity such entities. This we need to knowbefore doing the normalization process. From the results it can be describednormalization databsenya logic model, and this is a foundation in database designstep further.